Hubungan antara Secure Attachment dengan Kemandirian pada Siswa Kelas XI - Ifani Candra; Khansha Ulya Leona (Psyche 165 Journal, 2019)
The purpose of this study aims to determine the relationship between secure attachment and independence in class X SMA / MA Ar-Risalah padang. The independent variable in this study is secure attachment and the dependent variable in this study is independence. The measuring instrument used in this study is the scale of the secure attachment and the scale of independence. The data collection technique in this study was a simple random sampling technique. The population in this study were grade X students of SMA / MA Ar-Risalah Padang, amounting to 192 people. The sample of the study was 115 students of class X SMA / MA ARRisalah Padang. The validity of thescale secure attachment moves from rix =0.326 to rix = 0.942 and reliability 0.952. For the scale of independence, move from rix = 0.322 to rix = 0.810 and reliability 0.952. The hypothetical test result is 0.312 with a significant level of 0.001 indicating there is a relationship between secure attachment and independence. The secure attachment amount ofwith independence is 10% and 90% is determined by other factors